Wastewater microbiology - Bitton, Gabriel (Hoboken, N.J. : Wiley-Blackwell, 2011)
"Wastewater Microbiology focuses on microbial contaminants found in wastewater, methods of detection for these contaminants, and methods of cleansing water of microbial contamination. This classic reference has now been updated to focus more exclusively on issues particular to wastewater, with new information on fecal contamination and new molecular methods. The book features new methods to determine cell viability/activity in environmental samples; a new section on bacterial spores as indicators; new information covering disinfection byproducts, UV disinfection, and photoreactivation; and much more"--Provided by publisher.
pt. A. Fundamentals of microbiology -- pt. B. Public health microbiology -- pt. C. Microbiology of wastewater treatment -- pt. D. Biotechnology in wastewater treatment -- pt. E. Fate and toxicity of chemicals in wastewater treatment plants -- pt. F. Microbiology and public health aspects of wastewater effluents and biosolids disposal and reuse.
Includes bibliographical references and index.
Description based on metadata supplied by the publisher and other sources.
Electronic reproduction. Santa Fe, Arg.: elibro, 2022. Available via World Wide Web. Access may be limited to eLibro affiliated libraries.
Keywords: Sanitary microbiology; Water -- Microbiology; Sewage -- Microbiology; Electronic books